Effect of Insulin Resistance on Cardiac mass in Elderly Normotensive people: A Cross-Sectional Study - Kamal, Amr; Mahmoud, Dina; Hemida, Kamel; Abdelaaty, Talaat (Cardiology and Cardiovascular Medicine, 2022)
Aim: To study the independent effect of insulin resistance on LVM in the elderly normotensive population. Methods: The study included 50 subjects excluding patients with myocardial infarction, heart failure, systemic hypertension and aortic stenosis. Group I included 30 patients with glucose intolerance, insulin resistance, or type 2 DM while Group II included 20 control subjects of matched age and sex. Participants involved in the study underwent clinical examination, laboratory investigation (including 75-g oral glucose tolerance test, HbA1c, Plasma insulin level, calculated HOMA-IR, Fasting Lipid profile, Serum albumin/creatinine ratio) and echocardiography. Results: LV mass index was significantly different between the 2 group being higher (142.07±53.34) in the study group compared to (92.05±9.42) in the control group, (P=0.000). Waist circumference, HOMA-IR, FBS, HbA1c and systolic BP have significant positive correlations with LV mass index. However, only HOMA-IR has a significant independent positive correlation with LV mass index. Conclusion: It is inferred from the present study that insulin resistance is associated with increased cardiac mass in normotensive elderly people.